Improvement of structural, physicochemical, and rheological properties of porcine myofibrillar proteins by high-intensity ultrasound treatment for application as Pickering stabilizers - Yun Jeong Kim; Min Hyeock Lee; Se-Myung Kim; Bum-Keun Kim; Hae In Yong; Yun-Sang Choi (Ultrasonics Sonochemistry, 2023)
This study aimed to evaluate the potential of time-dependent (0, 15, 30, 60, 120 min) treatment of porcine-derived myofibrillar proteins (MPs) with high-intensity ultrasound (HIU) for utilizing them as a Pickering stabilizer and decipher the underlying mechanism by which HIU treatment increases the emulsification and dispersion stability of MPs. To accomplish this, we analyzed the structural, physicochemical, and rheological properties of the HIU-treated MPs. Myosin heavy chain and actin were observed to be denatured, and the particle size of MPs decreased from 3,342.7 nm for the control group to 153.9 nm for 120 min HIU-treated MPs. Fourier-transformed infrared spectroscopy and circular dichroism spectroscopy confirmed that as the HIU treatment time increased, α-helical content increased, and β-sheet decreased, indicating that the protein secondary/tertiary structure was modified. In addition, the turbidity, apparent viscosity, and viscoelastic properties of the HIU-treated MP solution were decreased compared to the control, while the surface hydrophobicity was significantly increased. Analyses of the emulsification properties of the Pickering emulsions prepared using time-dependent HIU-treated MPs revealed that the emulsion activity index and emulsion stability index of HIU-treated MP were improved. Confocal laser scanning microscopy images indicated that small spherical droplets adsorbed with MPs were formed by HIU treatment and that dispersion stabilities were improved because the Turbiscan stability index of the HIU-treated group was lower than that of the control group. These findings could be used as supporting data for the utilizing porcine-derived MPs, which have been treated with HIU for appropriate time periods, as Pickering stabilizers.